Educação física escolar: percepções sobre a eficácia do curso de capacitação do Comitê Paralímpico Brasileiro - Ranzan, Mayara Erbes (Universidade Federal de São Carlos, 2022)
The training process in the initial Physical Education courses, and specifically in the context of future work with students with disabilities, has its history marked by challenges. One of these challenges is to provide sufficient opportunities for knowledge and experiences for academics to serve each and every public. Therefore, it is common for research to point out difficulties in professional performance when in the context of inclusive Physical Education. This reality can culminate in the search for continuing education, so that it gives support and contributes to solving the existing gaps. In this context, it is important and necessary to investigate the proposals for continuing education, gathering information about their actions and the consequences in the reality of those involved. Given this need, the present research aimed to analyze, through the evaluation of the participants, whether a training course developed by the Brazilian Paralympic Committee and carried out in a specific municipality provided a complementation in their training. The choice to analyze this course in question is justified by the relevance of the Brazilian Paralympic Committee in the context of sport and people with disabilities. This course took place in person and was divided into 5 modules, which took place on 5 different days lasting 8 hours each day, totaling 40 hours. The 8 hours a day were divided into theory and practice. The topics covered in the modules were: Introduction to the Paralympic movement; Sitting volleyball; goalball; Athletics and Bocce. After completing the course, those involved were invited to participate in the present research, which was characterized as a case study with mixed quali-quantitative analysis. The research had the participation of thirty-two people with different profiles between academics and teachers from different areas, but the area of Physical Education had the most representative number. Participants answered the data collection instrument, which was a questionnaire composed of 11 open questions, of which 10 were added to a numerical scale that ranged from zero to 10, with zero to two being the “bad” classification, three to five “average”, six to eight “good” and nine to 10 “excellent”. Through the data obtained and examined, it was possible to verify positive results, which met the objectives raised, answered the guiding question, confirmed the initial hypothesis and indicated that the course in question was considered an opportunity to update, complement and deepen the knowledge of the participants in the context of Physical Education classes in the inclusive perspective. Thus, it was found that the training processes are essential for a future professional performance of quality, indicating the need for investigations and continuous evaluations in studies and research around the theme.
School physical education: perceptions about the effectiveness of the Brazilian Paralympic Committee training course
Keywords: Inclusão; Educação física escolar; Formação de professores; Esporte paralímpico; Atividade física adaptada; Inclusion; School physical education; Teacher training; Paralympic sport; Adapted physical activity; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO